2017
DOI: 10.2337/dc16-2259
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Cytokines Predict the Incidence and Progression of Distal Sensorimotor Polyneuropathy: KORA F4/FF4 Study

Abstract: OBJECTIVEExperimental and epidemiological studies have implicated inflammatory processes in the pathogenesis of distal sensorimotor polyneuropathy (DSPN), but prospective studies are lacking. We hypothesized that biomarkers of inflammation predict the development and progression of DSPN in a population-based cohort. RESEARCH DESIGN AND METHODSThis study was based on participants aged 62-81 years from the Cooperative Health Research in the Region of Augsburg (KORA) F4/FF4 cohort, with a mean follow-up of 6.5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
98
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(135 citation statements)
references
References 41 publications
(67 reference statements)
13
98
2
2
Order By: Relevance
“…In addition to these inflammatory molecules, circulating and locally produced ICAM‐1, vascular cell adhesion molecule‐1, E‐selectin and chemokines have increased expression in diabetes and DPN, and have been shown to be associated with the development and progression of DPN only by cross‐sectional trials. Although, in this prospective study6, it was reported that IL‐6 and TNF‐α elevation increased DPN development, and elevation of the levels of these systemic cytokines is not specific to DPN, but is observed in cardiovascular disease, obesity and other diabetic complications, such as diabetic nephropathy. Therefore, we should confirm the difference in systemic cytokine change between DPN and other low‐grade inflammatory disease6.…”
mentioning
confidence: 65%
See 4 more Smart Citations
“…In addition to these inflammatory molecules, circulating and locally produced ICAM‐1, vascular cell adhesion molecule‐1, E‐selectin and chemokines have increased expression in diabetes and DPN, and have been shown to be associated with the development and progression of DPN only by cross‐sectional trials. Although, in this prospective study6, it was reported that IL‐6 and TNF‐α elevation increased DPN development, and elevation of the levels of these systemic cytokines is not specific to DPN, but is observed in cardiovascular disease, obesity and other diabetic complications, such as diabetic nephropathy. Therefore, we should confirm the difference in systemic cytokine change between DPN and other low‐grade inflammatory disease6.…”
mentioning
confidence: 65%
“…Although, in this prospective study6, it was reported that IL‐6 and TNF‐α elevation increased DPN development, and elevation of the levels of these systemic cytokines is not specific to DPN, but is observed in cardiovascular disease, obesity and other diabetic complications, such as diabetic nephropathy. Therefore, we should confirm the difference in systemic cytokine change between DPN and other low‐grade inflammatory disease6.…”
mentioning
confidence: 65%
See 3 more Smart Citations